Effects of three-dimensional femur and tibia postures on the parameters of standing long-leg radiographs for osteoarthritic knees in elderly female subjects - Otani, Kazutaka; Sato, Takashi; Kobayashi, Koichi; Mochizuki, Tomoharu; Tanifuji, Osamu; Katsumi, Ryota; Kawashima, Hiroyuki (Clinical biomechanics (Bristol), 2024)
Long-leg frontal radiographs of the lower extremities are used to assess knee osteoarthritis. Given the three-dimensional (3D) nature of alignment changes in osteoarthritis, postural alterations in the femur and tibia extend beyond the coronal plane (in-plane) to include the transverse and sagittal planes (out-of-plane). This study investigates the impact of these out-of-plane factors on in-plane knee alignment parameters observed in frontal radiographs. A total of 97 osteoarthritic knees in women were examined. Using a 3D-to-two-dimensional (2D) image matching technique, we evaluated the 3D postures of the femur and tibia in the standing position as viewed from frontal radiographs in the world coordinate system. Statistical analyses were conducted to explore associations between these 3D postures and 2D alignment parameters obtained from frontal radiographs under identical conditions. The femur exhibited a medial inclination of 2.7°, a posterior inclination of 3.9°, and an internal rotation of 4.2°, whereas the tibia showed a lateral inclination of 6.4°, an anterior inclination of 6.7°, and an internal rotation of 6.7°. Both coronal and rotational postures of femur and tibia influenced the hip-knee-ankle angle, mechanical axis percentage, and medial proximal tibial angle. However, only coronal factors of tibia impacted tibial joint line obliquity relative to the floor. Attention should be paid to the potential impact of the out-of-plane postures of the femur and tibia on parameters assessed in plain frontal radiographs of the lower extremities. •We three-dimensionally assess lower limb alignment in weight-bearing conditions.•Both coronal and rotational factors affect long-leg alignment parameters.•The tibial joint line obliquity was only related to postures in the coronal plane.